The quality and safety of food contact materials – paper and cardboard coated with paraffin emulsion. (November 2018) - Nowacka, M.; Rybak, K.; Wiktor, A.; Mika, A.; Boruszewski, P.; Woch, J.; Przybysz, K.; Witrowa-Rajchert, D.
Abstract: The aim of this study was to assess the quality of paper and cardboard coated with different emulsions as food contact materials. The paper and cardboard were covered (impregnated) with a single layer of three different emulsions produced using paraffin and waxes, varying in content of dry matter, pH and emulsifiers. The organoleptic properties, overall and specific migration expressed as cadmium and lead content, were evaluated. Moreover, the water and oil contact angle and samples' microstructure were analyzed in order to determine the resistance of materials to moisture and grease penetration. The analysis of scanning electron microscope (SEM) images indicated that some of the examined emulsions penetrated the material, and others created a layer of coating. Impregnation of paper and board caused a change in smell, but did not influence the taste of food used to test the impact on sensorial properties. It is worth emphasizing that overall migration limit was not exceeded in the case of all investigated samples. The samples impregnated with emulsions were characterized as having better water (including water vapour) and oil resistance in comparison with the non-coated ones. Highlights: The safety of paper and cardboard impregnated with paraffin emulsion were studied. Impregnated paper and board samples complied the overall migration limit. Emulsions coating caused better water vapor, water and oil resistant. Emulsions composition allowed to determine the ability to form a coating layer.